2011
DOI: 10.3113/fai.2011.0616
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Standard Fluoroscopy in Detecting Rotational Malreduction of the Syndesmosis in an Ankle Fracture Model

Abstract: In the setting of ankle fractures with syndesmosis disruption, fixing the fibula in as much as 30 degrees of external rotation may go undetected using intraoperative fluoroscopy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 26 publications
2
75
0
2
Order By: Relevance
“…Direct visualization and open reduction of the syndesmosis has been recommended (Miller et al 2009), since lateral translation and rotational malalignment of the fibula at the level of the syndesmosis may go underdetected (Marmor et al 2011). This is reflected in our findings, since the majority of reoperated cases were due to syndesmotic malreduction (III).…”
Section: Recognition Of "Red Flags"supporting
confidence: 66%
“…Direct visualization and open reduction of the syndesmosis has been recommended (Miller et al 2009), since lateral translation and rotational malalignment of the fibula at the level of the syndesmosis may go underdetected (Marmor et al 2011). This is reflected in our findings, since the majority of reoperated cases were due to syndesmotic malreduction (III).…”
Section: Recognition Of "Red Flags"supporting
confidence: 66%
“…Despite the previous confirmation that plain radiographs provide an inaccurate assessment of syndesmotic reduction, plain radiographs provide the easiest, most cost-saving, method of longitudinal evaluation of implants and bone position. 20 Additionally, the clinical significance of the 1-mm difference between final MCS in the 2 groups may not be determined until 10-20 years of clinical follow-up. These radiographs provide a cheaper assessment of ankle congruency and the presence of postoperative arthritis with prolonged follow-up, as well as a decreased radiation burden.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has shown syndesmotic malreductions to occur in as many as 25.5% to 52% of patients. 66,75,76,102,109,110 The malpositioning is often in the sagittal plane with anterior displacement and internal rotation. [108][109][110] Predictors of malreduction have been investigated, but no significant factors could be elucidated.…”
Section: Surgeon Factorsmentioning
confidence: 99%
“…A cadaveric study suggested that a 30 external malrotation of the fibula may result when using TFCS, TFO, and posterior subluxation to assess reduction. 102 Because of these difficulties, surgeons have attempted to compare the injured side with a normal contralateral extremity. 103,104 Although substantial variation in ankle anatomy exists between individuals, there is little variation between contralateral ankles of a single individual.…”
Section: Assessment Of Reductionmentioning
confidence: 99%